Online religious information seeking behaviour among Mexican female muslim converts - Meza, Gabriela Aurora Mondragon (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University, 2020)
This study is about online religious information seeking behavior among Mexican female Muslim converts using theoretical concepts of information seeking behavior and the Sense-Making Theory developed by Dervin (1983). The respondents of this study were fourteen Mexican female Muslim converts living in a non-Muslim country, Mexico, where they face the day-to-day challenge of how to be a Muslim in a non-Islamic environment and belonging to Catholic families. These are further compounded by the misconception and hysteria created by the mass media about Islam and its followers. The research objectives of the study are: (1) To investigate the experience of Mexican female Muslim converts in their process of online religious information seeking; (2) to identify the information needs among them; and (3) to explore their information use. A qualitative methodology was used, utilising online narrative interviews through WhatsApp. The ATLAS.ti software was used for data management and analysis. The researcher found that there are two different processes of information seeking behavior: before and after conversion. Information needs and information use are different in each step for the respondents. The researcher found why the respondents look for online religious information, what are their needs, and how they use the information. It was also found that the society was not prepared for the changes undertaken by a Muslim convert in practising the discipline and religion of Islam. The present research has several contributions. It adds to the existing body of knowledge in four areas: namely communication, information seeking behavior, Internet studies and in the context of minority Muslims. This work can serve as a future reference in research on communication looking for literature on Muslim converts, particularly involving Mexican convers, as well information on male converts.